The Impact of Using Immersive Virtual Reality Technology on Children's Communication Skills in Kindergartens in Padang City - Ummayah, Yasifa Arkanasya; Nurhafizah Nurhafizah; Farida Mayar; Nenny Mahyuddin (Universitas Pendidikan Ganesha, 2025)
The rapid development of technology has not been fully optimized in early childhood education, particularly in developing children’s communication skills. In the digital era, mastery of modern technology is a potential means to support the stimulation of children's social and communication abilities. This study aims to examine the effectiveness of immersive virtual reality technology in enhancing early childhood communication skills. This research employed a quantitative approach with a Quasi-Experimental design using a Non-equivalent Control Group Design. The study involved 181 children selected through random sampling techniques. Data were collected using questionnaires, interviews, and documentation, and analyzed through prerequisite tests and t-tests. The results indicated a significant improvement in children's communication skills after receiving treatment with immersive virtual reality technology, with the average pre-test score increasing from 18.35 to 27.35 in the post-test. The t-test result obtained a significance value of 0.048 (p < 0.05), indicating a significant difference in communication skills between the experimental and control groups. These findings suggest that immersive virtual reality has the potential to be an effective innovative learning medium for developing early childhood communication skills. The implication of this research recommends integrating immersive technology into early childhood education programs to optimally support socio-emotional development.